Crise e vulnerabilidade social : uma leitura territorial - Marques, Teresa Sá (2016)
Like other countries in Southern Europe, Portugal is in a situationof economic crisis, with consequences in increased risks and socialvulnerability. The available indicators to measure its social impacts arestill relatively insufficient. The research presented here is developed,first at a national level and is based on a large number of indicators.In following we do a brief reflection of the social policies implementedin recent years. In the end, we move to a territorial analysis, tobuild a social geography focused on the number of people affectedby the crisis. It is a geography that reflects the situation in 2007 and2014, showing the strong geographical concentration of populationsin situations of greater social vulnerability. The presented picture willhave another social and territorial reading if the values were relativizedby population size, but that would be another analytical option.